Poly(acrylic acid) surface grafted polypropylene films: Near surface and bulk mechanical response (eXPRESS Polymer Letters)
Radical photo-grafting polymerization constitutes a promising technique for introducing functional groups onto surfaces of polypropylene films. According to their final use, surface grafting should be done without affecting overall mechanical properties. In this work the tensile drawing, fracture and biaxial impact response of biaxially oriented polypropylene commercial films grafted with poly(acrylic acid) (PAA) were investigated in terms of film orientation and surface modification. The variations of surface roughness, elastic modulus, hardness and resistance to permanent deformation induced by the chemical treatment were assessed by depth sensing indentation. As a consequence of chemical modification the optical, transport and wettability properties of the films were successfully varied. The introduced chains generated a PAA-grafted layer, which is stiffer and harder than the neat polypropylene surface. Regardless of the surface changes, it was proven that this kind of grafting procedure does not detriment bulk mechanical properties of the PP film.